Recent advance in the C–F bond functionalization of trifluoromethyl-containing compounds - Guobing Yan; Qiu, Kaiying; Guo, Ming (Organic chemistry frontiers an international journal of organic chemistry, 2021)
The C–F bond is the strongest single bond in organic compounds. It is the most challenging task to study the activation of the C–F bond in organic synthesis. Trifluoromethyl-containing compounds, which have three equivalent C–F bonds, constitute possible starting materials for the synthesis of diverse fluorinated compounds through selective C–F bond activation. In the past decades, significant progress has been made in the C–F bond activation of trifluoromethyl-containing compounds, mainly including trifluoromethylalkenes, trifluoromethylated aromatic and alkyl compounds, trifluoromethylketones, diazo compounds and N-tosylhydrazones of trifluoromethyl ketones, alkyltriflones, etc. In this review, we systematically summarized the C–F bond functionalization of these trifluoromethylated compounds, and their mechanisms were also discussed.